Geospatial Modeling of Megathrust Earthquake Hazards in Southern Java, Indonesia using GIS-Based Weighted Overlay Analysis - Aditya Dimas Dewanto; Noviyanti Riendrasiwi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Megathrust earthquakes occurring along subduction zones pose significant natural hazards, particularly in tectonically active regions such as Indonesia. The southern coast of Java is highly vulnerable due to its proximity to the Sunda megathrust, which has the potential to generate large-magnitude earthquakes and associated risks. This study aims to develop a GIS-based model to assess megathrust earthquake hazards in Southern Java, Indonesia. A quantitative geospatial approach was employed by integrating Geographic Information Systems (GIS) with a Multi-Criteria Decision Analysis framework using weighted overlay analysis. Several spatial parameters, including seismic activity, distance to the subduction zone, geological structure, and elevation, were processed and standardized before being combined into a composite hazard index. The results indicate a clear spatial pattern, where high hazard zones are concentrated in coastal and offshore areas near the subduction interface, while inland regions exhibit lower hazard levels. This spatial distribution reflects the influence of tectonic proximity on hazard intensity. The study demonstrates that GIS-based weighted overlay analysis is effective in integrating multiple hazard indicators into a unified spatial model. The resulting hazard map provides valuable insights for disaster risk reduction, spatial planning, and preparedness strategies in megathrust-prone areas. This research also contributes to the advancement of geospatial modeling frameworks for earthquake hazard assessment, particularly in regions with similar tectonic characteristics.